Respuesta :

Answer and Step-by-step explanation:

For this equation the answer is : [tex]n=3[/tex]

Step 1 : Simplify both the sides of the equation :

[tex]-2(7n-6)+n=-3-8n[/tex]

[tex](-2)(7n)+(-2)(-6)+n=-3+-8n[/tex]   (Distribute)

[tex]-14n+12+n=-3+-8n[/tex]

[tex](-14n+n)+(12)=-8n-3[/tex]   (Combine the like terms)

[tex]-13n+12=-8n-3[/tex]

[tex]-13n+12=-8n-3[/tex]

Step 2 : Add "[tex]8n[/tex]" to both the sides :

[tex]-13n+12+8n=-8n-3+8n[/tex]

[tex]-5n+12=-3[/tex]

Step 3 : Subtract "[tex]12[/tex]" from both the sides :

[tex]-5n+12-12=-3-12[/tex]

[tex]-5n=-15[/tex]

Step 4 : Divide both the sides by "[tex]-5[/tex]"

[tex]\frac{-5n}{-5} =\frac{-15}{-5}[/tex]

[tex]n=3[/tex]

That's your final answer : [tex]n=3[/tex]

gmany

Answer:

n = 3

Step-by-step explanation:

[tex]-2(7n-6)+n=-3-8n\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\(-2)(7n)+(-2)(-6)+n=-3-8n\\\\-14n+12+n=-3-8n\qquad\text{subtract 12 from both sides}\\\\(-14n+n)+12-12=-3-12-8n\\\\-13n=-15-8n\qquad\text{add}\ 8n\ \text{to both sides}\\\\-13n+8n=-15-8n+8n\\\\-5n=-15\qquad\text{divide both sides by (-5)}\\\\\dfrac{-5n}{-5}=\dfrac{-15}{-5}\\\\\huge\boxed{n=3}[/tex]

ACCESS MORE